PEMBELAJARAN MENULIS TEKS PUISI MENGGUNAKAN METODE THINK TALK WRITE ( TTW) BERBANTUAN MEDIA AUDIO VISUAL PADA SISWA KELAS X SMK BINA INSAN BANGSA NGAMPRAH - Ratna Wulan; Rochmat Tri Sudrajat; Dida Firmansyah (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
This study aims to determine students’ interest in learning, especially in writing poetry texts. Students are very difficult in terms of developing an idea or ideas into written form. The methods used by the teacher are sometimes less attractive sometimes less effective. As for the purpose of this study: 1) to know the scenario and implementation in writing poetry texts with method think talk write based audio visual  in class X student of  SMK Bina Insan Bangsa ; 2) to determine the response of teachers and students in writing in writing poetry texts by method think talk write based media audio visual in class X student of  SMK Bina Insan Bangsa; 3) to know the obstacles in writing poetry texts by method think talk write based media audio visual in class X student of  SMK Bina Insan Bangsa. The method used is descriptive qualitative  with samples student research in class X student of  SMK Bina Insan Bangsa. Learning to write poetry texts by using the method think talk write  assisted by media audio visual goes well scenarios and their implementation very suitable. Teacher and student against learning write excellent poetry texts. Difficulty from the lowest knowledge result 20 from 100 about disclosure and while the lowest average skill score is 65 less than 100 the contents of the language. From 37 students exist 26 students who get a value above average, KKM= 75  by percentage 95% very high category is declared passed.